Insights into participation in ward rounds in hospitals: A survey of clinical pharmacists' perceptions - Najmaddin A. H. Hatem; Seena A. Yousuf; Mohamed Izham Mohamed Ibrahim; Gubran S. Al-Galal (Taylor & Francis Group, 2024)
Introduction Clinical pharmacists' participation in ward rounds (WRs) has been a great chance to contribute to team-based care in the hospital setting and significantly improve patient outcomes and quality of life. Hence, the objective of this investigation was to explore the perceptions of clinical pharmacists in Yemen regarding their participation in WRs and the factors influencing their involvement. Methods An online survey of Yemeni clinical pharmacists was conducted and lasted for two months. Descriptive statistics were used to analyse the survey responses. Results a total of 120 participants were involved. About 3 out of 10 pharmacists had not previously participated in WRs, with only 30% having always or most of the time participated in word rounds alongside physicians. The results showed a positive perception of WR participation, with a median and IQR of 5(4-5). However, a lack of awareness of WR roles and the time-consuming nature of participation were the reasons for non-involvement. Conclusion The study highlights the positive perceptions of Yemeni clinical pharmacists towards ward rounds, but emphasises the need to address awareness and time constraints. Emphasising patient-centered care and longer internship durations can improve clinical pharmacist involvement. Future research should focus on optimising clinical pharmacist participation for better patient outcomes and care quality.